THE DEGREE OF COLORECTAL CANCER DIFERENTIATION AND INFILTRATION WITH TISSUE INTELEUKIN 6 EXPRESSION - Stanley Sugihwardojo; Bernadette Dian Novita; Imelda Theodora (FAKULTAS KEDOKTERAN UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2023)
Background: Colorectal cancer (CRC) is one of the most common malignancies reported in Indonesia, and it takes the fourth position as the most prevalent cancer just after lung carcinoma. Worldwide prevalence of CRC in 2020 is 34.189 cases, contributing to the 8.6% of all cancers reported. The diagnosis of nm is established through advanced examination such as colonoscopy, although other supporting examinations, consisted of occult blood test and histopathology examination are also performed to further evaluate the diagnosis. Pathogenesis of CRC involves the pro-carcinogenic factors (IL-6, IL-1 and TNFÎ±) accompanied by genetic mutation that predominate the anti-carcinogenic factors ; this pathological process underlies the occurrence of CRC.Objectives: This study aimed to analyze the correlation between the degree of colorectal adenocarcinoma differentiation and infiltration with tissue IL-6 expression.Methods: This study conducted observational analytic method with retrospective study design. The degree of colorectal adenocarcinoma differentiation and infiltration were identified through histopathological examination; the degree of tissue IL-6 expression was measured by the absorption rate of pigment containing anti-IL-6. Correlation test was performed by using Spearman Rank test on SPSS version 25.Results: There was a significant correlation between the degree of adenocarcinoma differentiation with tissue IL-6 expression (p = 0.039; < 0.05), but not with the degree of tumor infiltration (p = 0.129 ; > 0.05). Statistical test also showed negative, significant correlation between sex and IL-6 expression, indicating male predominance of IL-6 expression on colorectal adenocarcinoma cases ; this finding is supported with T-test that revealed significant difference of interleukin-6 expression between male and female sex.Discussion: The reported results in this study correspond with the previous studies conducted, except for the correlation between the tumor infiltration and interleukin-6 expression. Tumor infiltration along with its differentiation describe a complex process and influenced by various factors, including hormone, cytokines, and growth factors.Conclusion: Tissue IL-6 expression is correlated with the degree of colorectal adenocarcinoma differentiation, but not with the degree of infiltration.